2010
DOI: 10.1016/j.ijrobp.2010.07.1438
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality Local Therapy for Retroperitoneal Sarcoma

Abstract: 2016-12-24T18:13:07

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
1
12
1
Order By: Relevance
“…32 An earlier single-institution series showed that margin status was the only significant prognostic factor for 5-year OS, suggesting improving LC is likely related to improved OS. 33 These conclusions are consistent with previously mentioned SEER analyses of patients with STS of the extremities in which RT is only associated with an OS benefit to patients with high-grade disease. 21,22 This agrees with a prior SEER report of all patients with RPS, irrespective of tumor grade, which showed that adjuvant RT was associated with an increase in OS only in patients with malignant fibrous histiocytoma (although it should be noted that, in 2002, the World Health Organization declassified malignant fibrous histiocytoma and replaced it with high-grade undifferentiated pleomorphic sarcoma).…”
Section: Discussionsupporting
confidence: 90%
“…32 An earlier single-institution series showed that margin status was the only significant prognostic factor for 5-year OS, suggesting improving LC is likely related to improved OS. 33 These conclusions are consistent with previously mentioned SEER analyses of patients with STS of the extremities in which RT is only associated with an OS benefit to patients with high-grade disease. 21,22 This agrees with a prior SEER report of all patients with RPS, irrespective of tumor grade, which showed that adjuvant RT was associated with an increase in OS only in patients with malignant fibrous histiocytoma (although it should be noted that, in 2002, the World Health Organization declassified malignant fibrous histiocytoma and replaced it with high-grade undifferentiated pleomorphic sarcoma).…”
Section: Discussionsupporting
confidence: 90%
“…The majority of patients with PRPLS are diagnosed at an advanced disease stage, therefore PRPLS tumors often grow to a large size and have invaded adjacent organs upon diagnosis (22). The benefits of using adjuvant chemotherapy and radiation therapy to treat PRPLS remains controversial (23,24). A number of studies have suggested that chemotherapy may worsen patient prognosis (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested that chemotherapy may worsen patient prognosis (25,26). Other studies have reported that chemotherapy has limited effectiveness for PRPLS, but is beneficial for liposarcomas originating from the lower or upper extremities (23,27). Radiation can result in clinical complications, including nerve lesions, hydronephrosis, ureteral fistula and ileus (28).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike STS from the extremities in which approximately 90% local control is achieved largely through wide excision ± adjuvant radiotherapy (RT), the 5-year local control rate in RPS from surgical series ranges from 30 to 50% [2] and locoregional abdominal failure is the principle cause of death [3][4][5][6][7][8][9][10][11]. Efforts to improve local control in RPS have included the use of pre-operative RT (PreRT) [12][13][14]. This strategy produced 5 and 10-year relapse free survival rates of 69% and 63% respectively, in a Princess Margaret Cancer Centre (PMH)/Mt-Sinai Hospital Phase I/II study and has been adopted as standard practice at the PMH [15].…”
mentioning
confidence: 99%